Adolescence exposure to China’s great famine period and the association of metabolic syndrome in adulthood: a retrospective study - Sun, Ning; Li, Wei; Osibogun, Olatokunbo; Kalan, Mohammad Ebrahimi; Jebai, Rime; Gautam, Prem; Taskin, Tanjila; Yin, Wupeng; Jones, Jeffery A.; Gamber, Michelle; Sun, Wenjie (BMC public health, 2022)
Exposure to famine during early life is related to several adverse health outcomes in adulthood, but the effect of famine exposure during adolescence is unclear. This study aims to examine whether exposure to famine in adolescence is associated with metabolic syndrome (MetS) in adulthood. This study included 4130 Chinese adults (2059 males and 2071 females) aged 59-71 from the 2011 China Health and Retirement Longitudinal Study (CHARLS). All the selected participants were exposed to the three-year time period (1959-1961) of China's Great Famine. Participants were categorized into an adolescent-exposed group (born 01/01/1944-12/31/1948) and a non-adolescent-exposed group (born 01/01/1940-12/31/1941 and 01/01/1951-12/31/1952). Sex-stratified multiple logistic regression models were used to estimate the association between exposure to famine in adolescence and MetS. Participants exposed to famine during adolescence were more likely to report MetS (aOR = 1.35; 95%CI 1.01-1.78) compared to the non-adolescent-exposed group. Further, males were 45% less likely to report MetS than females (aOR = 0.55; 95%CI 0.36-0.83). After stratification by sex, the effects of famine exposure during adolescence on MetS were detected among males only (aOR = 1.97; 95%CI 1.20-3.24). Additionally, males with a history of drinking were more likely to report MetS compared to those with no history of drinking (aOR = 2.63; 95%CI 1.41-4.90). Our findings reveal that exposure to famine during adolescence is associated with higher odds of MetS in adulthood overall, and this association is only pronounced among males. This study emphasizes that undernutrition in early life, including adolescence, may have a long-term effect and be associated with adverse health events in middle-to-late life. Targeting those elderly people who suffered famine during adolescence may help prevent the development of MetS in later life.